Analysis of phenotype and genotype in 12 Chinese patients with Gitelman syndrome - Liu Tao; Gou Jia-kun; Lu Zuo-wei; Wei Hui-gang; Fang Yu-jie (Linchuang shenzangbing zazhi)
ObjectiveTo explore the clinical and genetic characteristics of Chinese patients with Gitelman syndrome （GS） and take new evidence into further understanding of this disease.MethodsFrom January 2019 to December 2020，patients diagnosed as GS by clinical and SLC12A3 gene examination and their family members were included.Clinical data were reviewed.High-throughput sequencing was performed for detecting potential variants.And Sanger’s sequencing was employed for verifying the results.Clinical characteristics and genetic variants were analyzed.ResultsA total of 12 pedigrees were included.All patients showed hypokalemia，hypomagnesemia，and hypocalciuria.Four patients developed hypochloremic metabolic alkalosis.There were diabetes （n=1） and prediabetes （n=1）.At emergency department，2 cases of recurrent palpitation were treated.The diagnoses were paroxysmal ventricular tachycardia and frequent premature ventricular complexes.Among 19 gene variants，the common variants were c.179C>T（3/12），c.1456G>A（2/12） and c.2582G>A（2/12）.The unreported novel variants were c.2178+1G>T and exon （4~6） deletion.During follow-ups，2 patients had normal serum levels of potassium or magnesium.ConclusionTwo novel variants are detected.Rectifying hypokalemia and hypomagnesemia remains difficult in GS patients.However，clinical symptoms may improve to varying degrees.Compared with general population，GS patients are at an elevated risk of glucose metabolism disorders.Due to severe hypokalemia and arrhythmia，GS patients with palpitations deserve more attention.